2020
DOI: 10.1002/hep4.1460
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and Pregnancy: Virologic and Immunologic Characteristics

Abstract: The hepatitis B virus (HBV) is an important human pathogen. Unvaccinated infants infected through mother-to-child transmission (MTCT) are at >95% risk of developing serum hepatitis B surface antigen-positive chronic hepatitis B (CHB). Despite complete passive-active HBV immunoprophylaxis, approximately 10% of infants born to mothers who are highly viremic develop CHB, and thus maternal treatment with nucleos(t)ide analogs (tenofovir disoproxil fumarate, lamivudine, or telbivudine) is recommended in the third t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 120 publications
0
66
0
Order By: Relevance
“…Our data suggest that post‐partum ALT flare after stopping tenofovir, may lead to more vigorous viral load suppression long term in those with a post‐partum ALT flare compared to those with no change in ALT. It is thought that reversal of immunotolerance to semi‐allogeneic foetal antigens following parturition is responsible for post‐partum hepatic flares in HBV infected women 15,16,20 . Other studies have demonstrated variable rates of ALT flares and HBeAg or HBsAg loss in late pregnancy and early post‐partum period among CHB carriers who stopped oral antivirals post‐partum, with the majority of flares resolving spontaneously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data suggest that post‐partum ALT flare after stopping tenofovir, may lead to more vigorous viral load suppression long term in those with a post‐partum ALT flare compared to those with no change in ALT. It is thought that reversal of immunotolerance to semi‐allogeneic foetal antigens following parturition is responsible for post‐partum hepatic flares in HBV infected women 15,16,20 . Other studies have demonstrated variable rates of ALT flares and HBeAg or HBsAg loss in late pregnancy and early post‐partum period among CHB carriers who stopped oral antivirals post‐partum, with the majority of flares resolving spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,14 Immune reconstitution post-partum can increase host immune-mediated flares to viral antigens, that is potentially exacerbated following withdrawal of TDF. 15,16 Most studies found that NA therapy in late pregnancy followed by treatment withdrawal early post-partum was associated with ALT flare but reported variable changes in HBV DNA levels or rates of HBeAg seroconversion during immediate post-partum up to 1 year of follow-up. 10,12,[17][18][19][20][21][22] The primary objective of this retrospective real-world cohort study was to evaluate maternal viral markers (ie HBV DNA, HBeAg and HBsAg) and ALT changes during pregnancy, early and long-term follow-up post-partum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mother-to-child transmission is still a main transmission route of HBV infection in China. Over 90% of the newborns who get infected HBV develop into chronic hepatitis B carrier status [ 9 , 10 ]. Infants infected by mother-to-child transmission could carry HBV for dozens of years [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preventative measures against HBV and HDV induced liver cancer include birth-dose vaccinations, hepatitis B immunoglobulin treatment for children born to infected mothers as well as treatment of mothers with high HBV viral load with nucleos(t)ide inhibitors in the third trimester[ 14 ]. For those individuals who are already chronic carriers of HBV/HDV, there is no virological cure; however, treatment with nucleos(t)ide analogs can lower the risk of HCC development[ 15 ].…”
Section: Introductionmentioning
confidence: 99%